Atraumatic Displaced Femoral Neck Fracture Postpartum: A Case Report and Review of the Literature. (September 2019) - Tayne, Samantha; Fralinger, David; Ali, Arif
Abstract : Hip pathology during pregnancy may include transient osteoporosis of the hip or osteonecrosis associated with pregnancy. Rarely, hip pathology during pregnancy may result in a fragility fracture or advanced collapse of the femoral head, necessitating surgical treatment. We present a case of a 32-year-old woman who postpartum was found to have a displaced right femoral neck fracture and an area of focal edema in the left femoral head with mild flattening of the articular surface. She was successfully treated with a total hip arthroplasty on the right, and a follow-up MRI of the left hip showed near-complete resolution of the edema in the femoral head. This case underlines the importance of maintaining a clinical suspicion for pathology of the hip during pregnancy and the subsequent consequences of a missed diagnosis.